Genetic diversity of mitochondrial DNA D-loop sequence in Bang Troi chicken breed - Nguyen, Thuy Thi Dieu; Dinh, Thi Ngoc Thuy; Mai, Thi Thanh Nga (Academia Journal of Biology, 2024)
Bang Troi chicken (GBT) is a local chicken that is free-gardening raised in Quang Ninh province. A 1,268 bp of mitochondrial DNA (mtDNA) D-loop of 17 Bang Troi chicken individuals was sequenced and analyzed. Comparative multiple sequence alignment revealed 17 base substitutions within 17 Bang Troi chicken individuals. Bang Troi chicken had a relatively high level of genetic diversity, expressed in the number of 13 haplotypes, haplotype diversity of 0.949. The Tajima’s test indicated that the analysed population in balancing selection with a D-value of 2.39. A phylogenetic tree based on 455 bp of hypervariable mtD-loop sequence classified 17 Bang Troi chicken individuals into three clades A, B, and E, which are common groups of Vietnamese and Asia indigenous chickens. This result provides the first genetic information and maternal lineages of Bang Troi chickens and it can support for registration of local chicken breeds.